Nanoparticle composite

By binding ligands on the surface of nanoparticles and using functional particles to form a condensed structure, the problem of ligand separation during heating is solved, and the weather resistance and stability of nanoparticles are improved.

CN119855783APending Publication Date: 2025-04-18SHOEI CHEM IND CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380064753.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-09
Filing Date
2023-09-07
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when heating a nanoparticle complex, the ligand is prone to detachment due to thermal vibration, resulting in the surface of the nanoparticles being eroded by moisture and oxygen, reducing its characteristics.

Method used

By binding ligands on the surface of nanoparticles and binding to nanoparticles through ligands using functional particles, agglomerated structures surrounded by functional particles are formed to stabilize the binding of ligands.

Benefits of technology

Effectively prevent ligand detachment, improve the weather resistance of nanoparticles, avoid thermal damage, and enhance their stability in different environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119855783A_ABST
    Figure CN119855783A_ABST
Patent Text Reader

Abstract

A nanoparticle composite according to an embodiment of the present invention is provided with: nanoparticles (11); the present invention relates to a nanoparticle composite having a structure in which the periphery of a nanoparticle is surrounded by a functional particle, a ligand (12) bonded to the nanoparticle, and a functional particle (13) bonded to the nanoparticle by means of the ligand, the nanoparticle composite having a structure in which the periphery of the nanoparticle is surrounded by the functional particle. In a nanoparticle composite according to another embodiment of the present invention, nanoparticles are enclosed in an aggregate structure (14) comprising a plurality of functional particles, and the nanoparticles and the aggregate structure are bonded by a ligand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to nanoparticle composites.

[0002] The present application claims priority based on Japanese Application No. 2022-144107 and Japanese Application No. 2022-144110 filed on September 9, 2022, and the contents of the Japanese Applications are incorporated into the present specification by reference. Background Art

[0003] Usually, nanoparticles have a large specific surface area, so it is easy to cause surface oxidation and aggregation according to the composition of the nanoparticles. In addition, among nanoparticles, especially quantum dots (QDs), the surface activity is high, and there is a problem of being easily degraded by reacting with moisture and oxygen in the atmosphere. In order to solve these problems, a lot of research has been carried out to protect the surface of quantum dots.

[0004] For example, Patent Document 1 discloses a method for manufacturing a quantum dot material, which comprises: mixing a core-forming metal complex with a nitrogen group element compound to form a nanocrystalline core material, adding a chlorine- and / or bromine-containing modifier to a solution containing the nanocrystalline core material, modifying the surface of the nanocrystalline core material by the modifier, mixing an outer shell-forming metal complex and a chalcogen compound in a solution containing the modified nanocrystalline core material, forming an outer shell on each of the modified nanocrystalline core materials, and modifying the surface of the outer shell by adding the modifier to the solution containing the nanocrystalline core material.

[0005] Patent Document 2 discloses quantum dots in which the surface of semiconductor crystal particles is modified with a ligand having two or more functional groups that interact with the semiconductor crystal particles and coordinated with two or more dentates, thereby improving stability.

[0006] Patent Document 3 discloses hydrophobic semiconductor fine particles, which are obtained by subjecting quantum dots coated with SiO2 to a hydrophobic treatment and are easily dispersed in an organic solvent or a resin.

[0007] Patent Document 4 discloses an inorganic nano-phosphor particle composite including inorganic nano-phosphor particles and inorganic fine particles attached to the surfaces of the inorganic nano-phosphor particles.

[0008] Quantum dots processed in this way are expected to be used as wavelength conversion materials for displays, biological markers for medical use, and solar cell materials.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: International Publication No. 2017 / 188300

[0012] Patent Document 2: Japanese Patent Application Publication No. 2019-099694

[0013] Patent Document 3: Japanese Patent Application Publication No. 2021-182025

[0014] Patent Document 4: Japanese Patent Application Publication No. 2018-080272

[0015] Non-patent literature

[0016] Non-patent document 1: Murray et al J. Am. Chem. Soc. 1993, 115, 8706-8715 Summary of the invention

[0017] Technical problem to be solved by the invention

[0018] As described above, in order to protect the surface of nanoparticles, a method of forming a nanoparticle composite by surface-treating the surface of nanoparticles with a substance different from the nanoparticles has been widely studied.

[0019] But, as the surface treatment of the nanoparticle based on part as recorded in patent documentation 2, because part is less than the tolerance of heat, therefore when heating nanoparticle complex, part easily breaks away from the nanoparticle surface because of thermal vibration.The position where part breaks away becomes the erosion point of moisture, oxygen, becomes the main reason that reduces the characteristic of nanoparticle.On the other hand, as the surface treatment of the nanoparticle utilizing oxide as recorded in patent documentation 3, also referred to as protective film or protective layer, mostly covers nanoparticle with the film of dense oxide.By covering the surface of nanoparticle with the film of dense oxide, can protect the surface of nanoparticle surely, but different from micron-level particle, be very difficult to form thin and uniform coating film on nanoparticle, this uneven coating position becomes the erosion point of moisture, oxygen, becomes the main reason that reduces the characteristic of nanoparticle.Or, when nanoparticle complex is used for application, under the situation that nanoparticle complex is stressed, cause the peeling of oxide film, the position of peeling becomes the erosion point of moisture, oxygen, becomes the main reason that reduces the characteristic of nanoparticle.

[0020] In addition, depending on the processing method, a heating process is sometimes required when forming an oxide layer or an oxide film. In this case, when forming an oxide layer or an oxide film, heat is applied to the nanoparticles themselves, which becomes the main reason for the nanoparticles to be thermally damaged and reduce the characteristics of the nanoparticles.

[0021] Therefore, an object of the present invention is to provide a nanoparticle composite in which a ligand is bound to the surface of the nanoparticle and the ligand is not easily detached.

[0022] Technical means of solving problems

[0023] The nanoparticle complex of the present invention comprises: a nanoparticle; a ligand, which is combined with the nanoparticle; and a functional particle, which is combined with the nanoparticle through the ligand, and the nanoparticle complex has a structure formed by the functional particle surrounding the nanoparticle. In addition, in the nanoparticle complex, the nanoparticle is enclosed in a cohesive structure composed of a plurality of functional particles, and the nanoparticle is combined with the cohesive structure through the ligand.

[0024] Effects of the Invention

[0025] According to the present invention, there can be provided a nanoparticle composite in which a ligand is bound to the surface of the nanoparticle and the ligand is not easily detached. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] [ Figure 1 ] Figure 1 This is a diagram schematically showing an example of the form of the nanoparticle composite according to the embodiment of the present invention.

[0027] [ Figure 2 ] Figure 2 This is a diagram schematically showing an example of the form of the nanoparticle composite according to the embodiment of the present invention.

[0028] [ Figure 3 ] Figure 3 This is a transmission electron microscope (TEM) image of the nanoparticle composite prepared in Experimental Example 1.

[0029] [ Figure 4 ] Figure 4 This is a graph showing the results of thermogravimetric analysis of the mass reduction of the nanoparticle composites and functional particle monomers prepared in Experimental Examples 1 and 9.

[0030] [ Figure 5A ] Figure 5A This is a graph showing the results of differential thermal analysis of the nanoparticle composite prepared in Experimental Example 9.

[0031] [ Figure 5B ] Figure 5B This is a graph showing the results of differential thermal analysis of the nanoparticle composite prepared in Experimental Example 1.

[0032] [ Figure 5C ] Figure 5C This is a graph showing the results of differential thermal analysis of the nanoparticle composite prepared in Experimental Example 10.

[0033] [ Figure 5D ] Figure 5D This is a graph showing the results of differential thermal analysis of the nanoparticle composite prepared in Experimental Example 11.

[0034] [ Figure 5E ] Figure 5E This is a graph showing the results of differential thermal analysis of the nanoparticle composite prepared in Experimental Example 12. DETAILED DESCRIPTION

[0035] The nanoparticle complex of the present invention comprises nanoparticles, ligands that bind to the nanoparticles, and functional particles that bind to the nanoparticles through the ligands, and the nanoparticle complex has a structure formed by a plurality of the functional particles surrounding the nanoparticles. The nanoparticles are enclosed in a cohesive structure composed of a plurality of functional particles, and the nanoparticles and the cohesive structure are bound through the ligands. In the present invention, the ligand has a binding group for the nanoparticles, and also has a binding group for the functional particles at other locations, and the ligand is bound to the surface of the nanoparticles through the nanoparticle binding group, and also is bound to the functional particles through the functional particle binding group.

[0036] The nanoparticle composite of the present invention has improved weather resistance compared to the composite described in Patent Document 2 in which the nanoparticle surface is treated only with a ligand, and can suppress the generation of corrosion points compared to the composite described in Patent Document 3, thereby obtaining practical weather resistance.

[0037] Figure 1 , Figure 2 1 shows an example of an embodiment of a nanoparticle complex. The nanoparticle complex is composed of a nanoparticle 11, a ligand 12, and a functional particle 13. Figure 1 As shown in FIG. 1 , the nanoparticle complex has a structure in which a plurality of the functional particles 13 surround the nanoparticle 11. The nanoparticle 11 is enclosed in a cohesive structure 14 composed of a plurality of the functional particles 13, and the nanoparticle 11 and the cohesive structure 14 are bound by a ligand 12. In addition, the nanoparticle complex of the present invention may have a structure as follows: Figure 2 The structure shown. The number of nanoparticles 11 contained in the condensed structure 14 does not have to be one, and a plurality of nanoparticles may be contained. The functional particle 13 may be bound to the plurality of nanoparticles 11 via the ligand 12.

[0038] It should be noted that Figure 1 or Figure 2 The structure of the nanoparticle complex shown is only an example and does not mean that the nanoparticle complex described in the present invention is limited to Figure 1 or Figure 2The structure recorded in .

[0039] Hereinafter, preferred embodiments will be described.

[0040] <Nano particles>

[0041] Nanoparticles constituting the nanoparticle composite of the present invention include metal nanoparticles, semiconductor nanoparticles (quantum dots), etc. The metal nanoparticles are not particularly limited, and particles with a particle size of 1nm to 100nm containing metals such as Ni and Ag, and alloys can be mentioned. Among nanoparticles, quantum dots are particularly susceptible to deterioration due to external factors, so the effect of the present invention can be enjoyed when the nanoparticles are quantum dots. In the present invention, quantum dots refer to nanoparticles of semiconductor crystals at the nanoscale with unique optical properties according to quantum mechanics of 1nm to 100nm. If it is a quantum dot, it is represented by quantum dots having the characteristics described in non-patent document 1, including quantum dots of group II-VI elements, group III-V elements, group IV elements, or group IV-VI elements, etc., but is not limited to these.

[0042] The particle size of the nanoparticles can be measured, for example, by calculating the particle sizes of 10 or more particles as area circle equivalent diameters (Heywood diameters) in a particle image observed by a transmission electron microscope (TEM).

[0043] <Ligand>

[0044] In the present invention, the ligand has a nanoparticle binding group and also has a functional particle binding group. These binding groups can be arranged at the ends of the main chain and the ends of the side chains. In addition, the ligand can be linear or branched. Preferably, the ligand is linear and preferably has each binding group at each end of the linear chain, and more preferably has each binding group at each end of the linear chain. This is because, when the ends of the linear chain, especially the ends, have binding groups, the movable area of ​​the functional particles below is expanded. The functional particle binding group is preferably more than one relative to one ligand, and its number is not particularly limited and can be multiple. Each ligand and each functional particle bound to them does not need to correspond one to one, and the ratio of the number of ligands to the number of functional particles can be, for example, 1000:1 to 1:200. The ratio of the number of ligands to the number of functional particles is preferably 1000:1 to 1:100, more preferably 500:1 to 1:50, further preferably 300:1 to 1:30, and most preferably 100:1 to 1:10, thereby suppressing the detachment of the ligand due to thermal vibration by pressing the ligand with the functional particles.

[0045] It should be noted that when the ratio of the number of ligands to the number of functional particles is close to 1:1, specifically 500:1 to 1:50, preferably 300:1 to 1:30, and more preferably 100:1 to 1:10. When the ratio of the number of ligands to the number of functional particles is close to 1:1, the functional particles can move flexibly, which is preferred.

[0046] In the present invention, nanoparticle binding group refers to the functional group combined with nanoparticles. As the type of combination, whether it is chemical combination or physical combination, specifically, coordination bond, covalent bond, hydrogen bond, hydrophobic interaction, physical adsorption can be enumerated, preferably a functional group that forms a strong combination with the nanoparticle surface. The nanoparticle binding group can for example enumerate thiol group (-SH) or amino group (-NH2), carboxyl group (-COOH), phosphate group, sulfo group, imino group, imido group, amide group, cyanate group etc. Depend on the composition on the surface of nanoparticle, particularly thiol group (-SH) or amino group (-NH2) can be more strongly combined with the nanoparticle surface, therefore preferred.

[0047] On the other hand, in the present invention, the functional particle binding group refers to a functional group combined with functional particles. As the type of combination, whether it is chemical combination or physical combination, specifically, coordination bond, covalent bond, hydrogen bond, hydrophobic interaction, physical adsorption can be cited, and it is particularly preferred to form a strong combination (for example, based on the bond of dehydration condensation, etc.) with functional particles. Depending on the surface state of functional particles, the functional particle binding group preferably includes a carboxyl (-COOH) or a hydroxyl (-OH). This is because, by including a carboxyl (-COOH) or a hydroxyl (-OH) through the functional particle binding group, the ligand can be more strongly combined with the functional particles. Although the mechanism is still uncertain, the inventors have found that when the ligand is more strongly combined with the functional particles, the ligand can be further suppressed from detaching from the nanoparticles.

[0048] The ligand is preferably a ligand with a small molecular weight. Due to the small molecular weight of the ligand, the physical distance between the nanoparticles and the functional particles becomes closer, and the volume of the nanoparticle complex can be further reduced. Specifically, the molecular weight of the ligand is preferably below 250. By suppressing the volume of the nanoparticle complex to be smaller, the content of the nanoparticle complex in the dispersion liquid, film, etc. containing the nanoparticle complex below can be increased. In addition, the molecular weight of the ligand is smaller so that the distance between the nanoparticles and the functional particles is physically close. According to the particle size of the functional particles, the condensed structure composed of the functional particles can form a dense structure that surrounds the nanoparticles. It will be described in detail below. As a dense structure, since the adjacent functional particles are basically not strongly combined with each other, when stress is applied to the nanoparticle complex from the outside, the functional particles can move flexibly and the stress can be relieved. This leads to the inhibition of the ligand from the nanoparticle.

[0049] According to described content, as the mode of particularly preferred part, be preferably to comprise thiol group in nanoparticle binding group, and comprise carboxyl or hydroxyl as the part of functional particle binding group, be the part that molecular weight is little.Specifically, can enumerate mercaptopropionic acid, thioglycolic acid etc..Can by using mercaptopropionic acid, thiolactic acid, thioglycolic acid, and suppress part to break away from nanoparticle, and then improve the containing rate of the nanoparticle complex in the dispersion liquid, film etc. that comprises nanoparticle complex hereinafter.

[0050] It should be noted that, in patent documentation 2, in order to improve the stability of nanoparticle, use the chelate type ligand with more than bidentate and nanoparticle coordination as part.In the past, think that with multidentate the surface of nanoparticle is coordinated and compared with single tooth the surface of nanoparticle is coordinated, can suppress the part from the nanoparticle surface to break away from, in the case that functional particle is combined with ligand as the present invention, in the case that single tooth has been carried out coordination, can suppress the part from breaking away from by functional particle, therefore do not necessarily need part to carry out coordination with multidentate to nanoparticle.That is, part of the present invention can be single tooth, can also be multidentate.In the case of single tooth, have the advantage that the movable region of functional particle expands.

[0051] <Functional Particles>

[0052] The functional particles are bound to the nanoparticles via the ligands and have a structure surrounding the nanoparticles. The functional particles are bound to the ligands via the functional particle binding groups.

[0053] Furthermore, with respect to one nanoparticle, the functional particles form an aggregate structure in which a plurality of functional particles are arranged around the nanoparticle via the ligand.

[0054] The particle size of the functional particles is preferably 1 nm to 100 nm. The nanoparticles can be effectively surrounded by making the particle size of the functional particles 1 nm to 100 nm. The particle size of the functional particles uses the average particle size (BET diameter) converted by the following method: the BET specific surface area is measured, and the average particle size (BET diameter) is converted from the value using a true sphere model.

[0055] The number of functional particles forming the aggregated structure is preferably 1 to 800, more preferably 2 to 600, and even more preferably 4 to 500, relative to one nanoparticle, based on the particle size of the nanoparticles and the functional particles. The aggregated structure composed of functional particles is 4 to 800 relative to one nanoparticle, thereby effectively enclosing the nanoparticles.

[0056] Functional particles can be inorganic or organic. Various properties can be imparted to the nanoparticle complex by selecting appropriate functional particles. The material selected as the functional particle can be only one kind or a combination of multiple kinds.

[0057] For example, when using a material with high reflectivity or refractive index as a functional particle, when applied to the following film, etc., it can be expected that the nanoparticle complex will be given a scattering agent. As functional particles with high refractive index, for example, titanium dioxide particles (TiO2), zinc oxide particles (ZnO), zirconium oxide (ZrO2), etc. can be cited.

[0058] The functional particles preferably have hydroxyl groups on the surface. The hydroxyl groups on the surface of the functional particles react with the functional particle binding groups of the ligands to inhibit the ligands from detaching from the nanoparticles. At this time, the ligands and the functional particles are preferably combined by dehydration condensation with strong binding force.

[0059] In addition, the functional particles may have an organic group that reacts with the ligand. By having an organic group on the surface of the functional particles, an organic solvent can be selected in the dispersion of the functional particles. This means that the selection range of functional particles is expanded.

[0060] As the organic group that reacts with the ligand, it is preferred to have an epoxy group. Although the epoxy group is an organic group, it can react with the functional particle-binding group of the ligand and can inhibit the detachment of the ligand from the nanoparticles.

[0061] In addition, can be by selecting suitable material as functional particles, and nanoparticle complex is given weatherability.Think that by functional particles and the ligand combination coordinated to the nanoparticle surface, functional particles press the ligand, can suppress the departure of the ligand, and the weatherability of nanoparticle complex improves thus.In this case, as functional particles, select the high inorganic particles of density, owing to the effect height of pressing the ligand, therefore preferably.

[0062] In the present invention, the inventors have found that, particularly when the functional particles are silicon dioxide particles (SiO2) or Si-containing particles, the weather resistance of the nanoparticle complex is improved. The mechanism is still unclear, and it is believed that the functional particle binding group of the ligand is strongly combined with the functional particle, thereby indirectly inhibiting the ligand from detaching from the nanoparticle surface.

[0063] Particularly when functional particles are silica particles or Si-containing particles, it is believed that the hydroxyl group on the surface is a part for silanol groups. The mechanism is still uncertain, and when the functional particle surface has silanol groups, it forms a stronger combination with the functional particle binding group of the part, so the nanoparticle complex has particularly high weather resistance. Si-containing particles, for example, can enumerate zirconium silicate, aluminum silicate, etc.

[0064] In the case of improving weather resistance, particles other than silica particles may be mixed as functional particles. For example, the silica particles and titanium dioxide particles may be mixed in a ratio corresponding to the purpose and use to form a cohesive structure so that the nanoparticles are enclosed. In this case, as the ratio of silica particles to functional particles other than silica particles, the volume ratio of silica particles to the whole functional particles is 10 vol.% or more, preferably 30 vol.% or more, more preferably 50 vol.% or more, and further preferably 70 vol.% or more, thereby improving the weather resistance of the nanoparticle complex.

[0065] Furthermore, in order to enhance the binding force between the functional particles and the ligand, a method of covering the surface of the functional particles with an arbitrary substance is conceivable.

[0066] In patent documentation 4, inorganic nano phosphor particle surface directly adheres to inorganic particles, and this processing is to finally make inorganic nano phosphor particles (nanoparticles) be scattered in the processing carried out in the glass matrix. Under the state that is only made of inorganic nano phosphor particles and inorganic particles, inorganic particles and inorganic nano phosphor particles are only physically adsorbed, and therefore easily break away from the surface of nano particle, particularly when applying stress, thermal vibration from the outside, do not have the part that nano particle and inorganic particles are firmly connected, if there is no glass matrix, then inorganic particles easily break away from the surface of nano particle, and therefore glass matrix is ​​necessary. On the other hand, in nano particle complex of the present invention, glass matrix can be arranged, and glass matrix can also be not arranged. There is no glass matrix to have the advantage that can make with easy method.

[0067] In the present invention, functional particles protect the surface of nanoparticles via part, therefore compared with the situation of directly covering the surface of nanoparticles with functional particles without part, functional particles have flexible mobility.Therefore, when stress can be applied to nanoparticle complex from the outside, functional particles, while maintaining the state of protecting nanoparticles, can relax stress by being flexible and removable, suppress part to break away from the nanoparticle surface.Even if any functional particle breaks away, also not only can maintain the protection of nanoparticles based on part, and because basically adjacent functional particles do not combine strongly each other, therefore the functional particles adjacent to the functional particles that break away move flexibly, cover the position that functional particles break away from, thus can avoid the fatal characteristic reduction of nanoparticle, can keep practical weather resistance as nanoparticle complex.

[0068] <Complex>

[0069] The nanoparticle complex of the present invention has a structure in which nanoparticles are enclosed in a cohesive structure, wherein the cohesive structure is composed of a plurality of functional particles and ligands, and the functional particles are combined with the nanoparticles through the ligands. Various functions can be imparted to the nanoparticle complex by selecting appropriate substances for the functional particles of the present invention.

[0070] In patent document 1, only the modification of the surface of nanoparticles is carried out by a modifier, and the process of improving dispersibility is not carried out, so the nanoparticles are easily condensed each other under the original state, and as a result, the luminescent characteristics may be reduced. The present invention, by adopting the structure, can suppress the condensation of nanoparticles each other, and can suppress the reduction of the luminescent characteristics caused by the condensation of nanoparticles.

[0071] In the present invention, since the nanoparticle composite adopts the above structure, the intervals between the nanoparticles are widened due to the physical contact between the functional particles, etc., and thus aggregation can be prevented.

[0072] The nanoparticle composite of the present invention can further improve weather resistance by including silica particles or Si-containing particles in the functional particles and having the above structure. In the present invention, the improvement of weather resistance means that the change rate of the fluorescent quantum efficiency based on the heat resistance / humidity resistance test described below is 90% or less, preferably 75% or less, more preferably 50% or less, further preferably 25% or less, and most preferably 21.4% or less.

[0073] In the past, when protecting nanoparticles with oxides, it was believed that a layer or film of oxide that was as dense as possible would preferably cover the entire nanoparticle. The present invention is based on the following new insight: the nanoparticles can be surrounded by a coagulated structure formed by multiple functional particles through ligands, thereby improving the weather resistance of the nanoparticles.

[0074] That is, the nanoparticle complex of the present invention presses the ligand by the functional particles, thereby not only being able to solve the problem of the ligand detachment of Patent Document 2, but also having the advantage that heat is not easily transferred to the ligand. In addition, unlike the oxide film of Patent Document 3, in the nanoparticle complex of the present invention, even if the functional particles somewhere detach, not only can the protection of the nanoparticles based on the ligand be maintained, and because the functional particles basically adjacent to the functional particles detach are not strongly combined with each other, the functional particles adjacent to the functional particles detached can move flexibly, covering the position where the functional particles detach, thus being able to avoid the fatal characteristic reduction of the nanoparticles.

[0075] In addition, the nanoparticle composite of the present invention has the following advantages: when stress is applied to the nanoparticle composite, the functional particles move flexibly, thereby relieving the stress, and when used for application, the degree of freedom of the process of handling the nanoparticle composite is increased.

[0076] It should be noted that the inventors believe that the binding strength between the functional particles can be adjusted as needed by changing the preparation conditions.

[0077] In addition, as the nanoparticle complex of the present invention, it is particularly preferred that the nanoparticles are quantum dots containing Zn on the surface, the ligand has a thiol group that can form a Zn-S bond on the surface of the nanoparticle as a nanoparticle binding group, and has a carboxyl group or a hydroxyl group as a functional particle binding group, and the functional particles are silica particles having hydroxyl groups, and particles other than silica may also be mixed. It should be noted that as quantum dots containing Zn on the surface of quantum dots, for example, there can be CdS / ZnSe with a core-shell structure in which a core is CdS and a shell is ZnSe, CdSe / ZnSe with a core-shell structure in which a core is CdSe and a shell is ZnSe, CdS / ZnSe / ZnS with a core-shell structure in which a first shell is ZnSe and a second shell is ZnS, CdSe / ZnSe / ZnS with a core-shell structure in which a core is CdSe and a first shell is ZnSe and a second shell is ZnS, InP / ZnSe with a core-shell structure in which a core is InP and a shell is ZnSe, and InP / ZnSe / ZnS with a core-shell structure in which a core is InP and a ZnSe shell is ZnS, but it is not limited to these.

[0078] In addition, the nanoparticle complex of the present invention has high acid resistance by having the structure. For example, the nanoparticle complex of Experimental Example 2 below can be confirmed to be luminescent after being immersed in hydrochloric acid of pH 1 for 3 hours. The experimental results under this condition mean that it can be actually used after oral administration and exposure to gastric acid in the human body. Therefore, the nanoparticle complex obtained by the present invention can be used as a medical marker.

[0079] <Evaluation of Weather Resistance>

[0080] Here, the fluorescence quantum efficiency of the nanoparticle complex can be measured using a fluorescence quantum efficiency measurement system (manufactured by OTSUKA ELECTRONICS, QE-2100) or the like. After the nanoparticle complex is loaded into a sample holder, it is irradiated with excitation light to obtain an emission spectrum. The fluorescence quantum efficiency (QY), peak wavelength (λmax), full width at half maximum (FWHM) and other optical properties can be calculated by removing the re-excitation fluorescence emission spectrum of the amount of fluorescence emitted by re-excitation from the emission spectrum obtained here, and then obtaining an emission spectrum after re-excitation correction. It should be noted that the excitation light used for the measurement is a single light of 450nm. In the heat resistance / humidity resistance test below, the numerical value of the fluorescence quantum efficiency (QY) measured at room temperature (25°C) is used to evaluate weather resistance.

[0081] The heat / humidity resistance test was conducted by keeping the nanoparticle complex in a constant temperature and humidity chamber at a temperature of 60°C and a relative humidity of 90% for 100 hours. The rate of change of the fluorescence quantum efficiency before and after the heat / humidity resistance test was calculated using the fluorescence quantum efficiency (QYa) before the heat / humidity resistance test and the fluorescence quantum efficiency (QYb) after the heat / humidity resistance test by the following calculation formula (1).

[0082] Fluorescence quantum efficiency change rate = {(QYa-QYb) / QYa}×100(1)

[0083] <Preparation method>

[0084] The method for producing a nanoparticle complex of the present invention comprises: a step of combining the nanoparticles with the ligand in a dispersion containing nanoparticles and ligands to obtain a precursor particle dispersion; and a step of mixing and reacting a dispersion containing functional particles with the precursor particle dispersion to obtain a nanoparticle complex dispersion in which the functional particles are combined with the nanoparticles via the ligands.

[0085] The nanoparticles are the nanoparticles described above and are not particularly limited. Examples thereof include metal nanoparticles such as Ni and Ag, and semiconductor nanoparticles (quantum dots).

[0086] The ligand is the ligand described above, having a nanoparticle binding group, and further having a functional particle binding group at other positions. These binding groups can be arranged at the ends of the main chain and the ends of the side chains. In addition, the ligand can be linear or branched. Preferably, the ligand is linear and preferably has each binding group at each end of the linear chain, and more preferably has each binding group at each end of the linear chain. This is because, at the end of the linear chain, especially at the end, there is a binding group, the movable area of ​​the functional particles below is expanded. The functional particle binding group is preferably more than one relative to one ligand, and its number is not particularly limited and can be multiple. Each ligand and each functional particle bound to them does not need to correspond one to one, and the ratio of the number of ligands to the number of functional particles can be, for example, 1000:1 to 1:200. The ratio of the number of ligands to the number of functional particles is preferably 1000:1 to 1:100, more preferably 500:1 to 1:50, further preferably 300:1 to 1:30, and most preferably 100:1 to 1:10, thereby suppressing the detachment of the ligand due to thermal vibration by pressing the ligand with the functional particles.

[0087] It should be noted that when the ratio of the number of ligands to the number of functional particles is close to 1:1, specifically 500:1 to 1:50, preferably 300:1 to 1:30, and more preferably 100:1 to 1:10. When the ratio of the number of ligands to the number of functional particles is close to 1:1, the functional particles can move flexibly, which is preferred.

[0088] Nanoparticle binding group refers to the functional group combined with nanoparticles. As the kind of combination, whether it is chemical combination or physical combination, specifically, coordination bond, covalent bond, hydrogen bond, hydrophobic interaction, physical adsorption can be enumerated, preferably the functional group that forms strong combination with nanoparticle surface. Nanoparticle binding group for example can enumerate thiol group (-SH) or amino group (-NH2), carboxyl group (-COOH), phosphate group, sulfo group, imino group, imido group, amide group, cyanate group etc. Depend on the composition on the surface of nanoparticle, particularly preferably thiol group (-SH) or amino group (-NH2).

[0089] On the other hand, the functional particle binding group refers to a functional group combined with functional particles. As the type of combination, whether it is chemical combination or physical combination, specifically, coordination bond, covalent bond, hydrogen bond, hydrophobic interaction, physical adsorption can be cited, and it is particularly preferred to form a strong combination (for example, a bond based on dehydration condensation, etc.) with functional particles. Depending on the surface state of the functional particles, the functional particle binding group preferably includes a carboxyl (-COOH) or a hydroxyl (-OH). This is because, by including a carboxyl (-COOH) or a hydroxyl (-OH) by the functional particle binding group, the ligand can be more strongly combined with the functional particles. The mechanism is still uncertain, and it is believed that by combining the functional particles with the ligand coordinated to the surface of the nanoparticles, the functional particles press the ligand, and the detachment of the ligand can be suppressed, thereby improving the weather resistance of the nanoparticle complex.

[0090] The ligand preferably has a small molecular weight. Because the molecular weight of the ligand is small, the physical distance between the nanoparticle and the functional particles becomes close, and the volume of the nanoparticle complex can be further reduced. By suppressing the volume of the nanoparticle complex to be smaller, the content rate of the nanoparticle complex in the dispersion liquid, film, etc. that contain the nanoparticle complex below can be improved. In addition, the molecular weight of the ligand is smaller so that the distance between the nanoparticle and the functional particles is physically close, and according to the particle size of the functional particles, the condensed structure formed by the functional particles can form a dense structure, surrounding the nanoparticles.

[0091] According to described content, as the mode of particularly preferred part, be preferably to comprise thiol group in the nanoparticle binding group, and comprise carboxyl or hydroxyl as the part of functional particle binding group, be the part that molecular weight is little.Specifically, can enumerate mercaptopropionic acid, thioglycolic acid etc..Can by using mercaptopropionic acid, thiolactic acid, thioglycolic acid, suppress part to break away from nanoparticle, and then improve the containing rate of the nanoparticle complex in the dispersion liquid, film etc. that comprise nanoparticle complex hereinafter.

[0092] In the dispersion liquid that comprises nanoparticle and part, described nanoparticle is combined with described part, obtain in the operation of precursor particle dispersion liquid, precursor particle dispersion liquid can use known method (for example ligand exchange method) after nanoparticle synthesis, specific part is combined with nanoparticle and obtain.Perhaps, can synthesize by adding specific part in nanoparticle synthesis, and make the nanoparticle after just synthesis be combined with specific part, thus obtain precursor particle dispersion liquid.

[0093] The dispersion containing the functional particles may be an aqueous dispersion containing water as the dispersion medium, or an organic solvent dispersion containing an organic solvent as the dispersion medium. It should be noted that a commercially available dispersion containing the functional particles may also be used.

[0094] The precursor particle dispersion is preferably a system having compatibility with the dispersion of the functional particles. For example, when the dispersion containing the functional particles is an aqueous dispersion, the precursor particle dispersion is also preferably aqueous. When the precursor particle dispersion is an organic solvent, the dispersion containing the functional particles is preferably an organic solvent.

[0095] Particularly when the functional particles are silica particles or particles containing Si, the functional particle dispersion and the precursor particle dispersion are preferably both aqueous. This is because, by making the dispersion containing the functional particles and the precursor particle dispersion both aqueous, and the presence of hydroxyl groups on the surface of the functional particles, the ligand and the functional particles are more easily combined.

[0096] The mixing method of the nanoparticle dispersion liquid and the dispersion liquid comprising functional particles is not particularly limited. The binding force of the part and the functional particles is strong, so it is possible to fully react by the stirring normally used. It should be noted that, as required, the binding strength of the part and the functional particles can be regulated by appropriately controlling the reaction environment.

[0097] It should be noted that the nanoparticle complex dispersion liquid that preferably makes functional particles be combined with the nanoparticle by the part is dried. As the drying method, it is not particularly limited, preferably heat drying, vacuum drying, freeze drying. Can obtain the nanoparticle complex that part and functional particles are further firmly combined by making the nanoparticle complex dispersion liquid be dried.

[0098] It should be noted that, as described above, the method for producing a nanoparticle complex of the present invention includes: a step of combining the nanoparticles with the ligand in a dispersion containing nanoparticles and ligands to obtain a precursor particle dispersion; and a step of mixing and reacting a dispersion containing functional particles with the precursor particle dispersion to obtain a nanoparticle complex dispersion in which the functional particles are combined with the nanoparticles through the ligand.

[0099] It should be noted that, not limited to this, the preparation method of nanoparticle complex of the present invention is as long as nanoparticle, part and functional particle can be reacted. Particularly by mixing nanoparticle and functional particle under the state of dispersion liquid, part can be combined with nanoparticle and functional particle more strongly, therefore preferably. As long as it is the method that comprises the dispersion liquid that comprises functional particle, part and the dispersion liquid that comprises nanoparticle mix and react the operation, then various methods can be adopted.

[0100] For example, the following method can be used: a ligand having a nanoparticle binding group that is bound to a nanoparticle and a functional particle binding group that is bound to a functional particle is mixed with the nanoparticle to obtain the nanoparticle that is bound to the ligand, and the nanoparticle that is bound to the ligand is mixed with the functional particle. By using this method, the nanoparticle that is bound to the ligand reacts with the functional particle to obtain a nanoparticle complex in which the functional particle is bound to the nanoparticle through the ligand.

[0101] In addition, the following method can also be used: a ligand having a nanoparticle binding group that is bound to a nanoparticle and a functional particle binding group that is bound to a functional particle is mixed with a functional particle to obtain a functional particle that is bound to the ligand, and the functional particle that is bound to the ligand is mixed with a nanoparticle. By using this method, the functional particle that is bound to the ligand reacts with the nanoparticle to obtain a nanoparticle complex in which the functional particle is bound to the nanoparticle through the ligand.

[0102] From the viewpoint of effectively surrounding the nanoparticles with the functional particles to form an aggregated structure, the above method is preferably used.

[0103] <Dispersion>

[0104] The nanoparticle composite of the present invention can be dispersed in any dispersion medium to prepare a dispersion liquid containing the nanoparticle composite.

[0105] <Film>

[0106] The nanoparticle composite of the present invention can be dispersed in any resin or matrix to form a film containing the nanoparticle composite.

[0107] Example

[0108] Method for manufacturing QD (CdSe / ZnSe / ZnS)

[0109] <Core Preparation (CdSe)>

[0110] First, selenium (0.79 g, 10 mmol) and trioctylphosphine (10.9 mL) were stirred at 150 ° C in an argon atmosphere for about 1 hour to completely dissolve the selenium and prepare a Se precursor. Next, cadmium acetate dihydrate (1.97 g, 7.5 mmol) and trioctylphosphine oxide (9.65 g) were added to a flask, and the flask was replaced with an argon atmosphere to prepare a Cd precursor. The Cd precursor was heated to 300 ° C, and 9.9 mL of Se precursor (containing 9 mmol of selenium) was added dropwise thereto at one time, and stirred for 5 minutes. After cooling to room temperature, butanol and methanol were used to remove unreacted Cd precursor and Se precursor, trioctylphosphine and excess trioctylphosphine oxide from the obtained reactant, and purified. The purified reactant was diluted with 10 mL of toluene to obtain a CdSe nanocrystal solution.

[0111] <Preparation of Shell (CdSe / ZnSe / ZnS)>

[0112] First, sulfur (0.32 g, 10 mmol) and trioctylphosphine (10.9 mL) were stirred at 150° C. for about 1 hour in an argon atmosphere to completely dissolve the sulfur and prepare an S precursor. 8 g of trioctylamine, 0.1 g of oleic acid, and 0.2 mmol of zinc acetate were placed in a flask and the reaction temperature was adjusted to 300° C. while stirring. After 0.1 mL of the formed CdSe nanocrystal solution was added to the reactants, 0.1 mL of Se precursor was added and the reaction was allowed to react for about 1 hour. Then, 0.1 mL of S precursor was added and the reaction was allowed to react for 1 hour.

[0113] After the reaction was completed, the temperature of the reaction mixture was lowered to room temperature as quickly as possible, ethanol was added as a non-reactive solvent, and centrifugation was performed. The supernatant of the solution from which the precipitate after centrifugation was removed was removed, and the precipitate was dispersed in toluene, thereby forming CdSe / ZnSe / ZnS (TEM diameter 15 nm).

[0114] A portion of the obtained nanoparticles was separated, dried, and observed using a transmission electron microscope (TEM). The particle sizes of 10 or more particles in the observed particle image were calculated as area circle equivalent diameters (Heywood diameters), thereby calculating the TEM diameter.

[0115] <Preparation of Precursor Particle Dispersion>

[0116] Mercaptopropionic acid (MPA: average molecular weight 106) was added to the obtained nanoparticle dispersion, and the mixture was heated to 120°C and stirred for 9 hours to exchange ligands. The solution was then cooled, and hexane was added for centrifugal separation. After separation into agglomerates and a supernatant, the supernatant, which was mainly composed of toluene and hexane, was removed. Acetone and hexane were then added and washed several times. Acetone and hexane were removed, water was further added, and an appropriate amount of tetramethylammonium hydroxide / methanol solution was added and stirred to prepare a nanoparticle dispersion in which nanoparticles were dispersed.

[0117] <Preparation of Nanoparticle Composite>

[0118] Experimental Example 1

[0119] As the dispersion containing the functional particles, a colloidal silica dispersion (Nissan Chemical Co., Ltd.: ST-OXS) was used.

[0120] The prepared precursor particle dispersion and the dispersion containing functional particles are separated and placed in a container for mixing. Then, the mixed solution (reaction solution) is dried by a dryer with the temperature adjusted to 50° C. to obtain a dried body. The dried body is crushed in a mortar, and the quantum efficiency of the obtained nanoparticle complex is measured.

[0121] Quantum efficiency is measured using a fluorescence quantum efficiency measurement system (QE-2100, manufactured by OTSUKA ELECTRONICS). After the nanoparticle complex is loaded into a sample holder, an excitation light (single light of 450 nm) is irradiated to obtain an emission spectrum. The fluorescence quantum efficiency (QYa) is calculated by removing the emission spectrum obtained here from the emission spectrum after the re-excitation correction of the re-excitation fluorescence emission spectrum of the amount of fluorescence luminescence that is re-excited.

[0122] Next, the heat / humidity resistance of the obtained nanoparticle complex was measured. The nanoparticle complex was placed in a constant temperature and humidity chamber (PHP-2J manufactured by ESPEC) set at a temperature of 60°C and a relative humidity of 90% and kept for 100 hours. After 100 hours, the fluorescence quantum efficiency (QYb) of the taken-out nanoparticle complex was measured again. In the present application, the rate of change of the fluorescence quantum efficiency before and after the heat / humidity resistance test is used as an indicator of weather resistance. As for the rate of change of the fluorescence quantum efficiency before and after the heat / humidity resistance test, the fluorescence quantum efficiency (QYa) before the heat / humidity resistance test and the fluorescence quantum efficiency (QYb) after the heat / humidity resistance test are used to calculate by the following calculation formula (1).

[0123] Fluorescence quantum efficiency change rate = {(QYa-QYb) / QYa}×100(1)

[0124] The change rate of the fluorescence quantum efficiency of the obtained nanoparticle complex is shown in Table 1.

[0125] Figure 3 This is a TEM (transmission electron microscope) observation image of the nanoparticle complex prepared in Experimental Example 1. The black particles are nanoparticles, and the gray particles are functional particles. A nanoparticle complex in which the nanoparticles are surrounded by the functional particles is observed.

[0126] Experimental Example 2

[0127] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that a colloidal silica dispersion (manufactured by Nissan Chemical: ST-O) was used as the dispersion containing the functional particles, and the properties were evaluated.

[0128] Experimental Example 3

[0129] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that a colloidal silica dispersion (Nissan Chemical Co., Ltd.: ST-O-40) was used as the dispersion containing the functional particles, and the properties were evaluated.

[0130] Experimental Example 4

[0131] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that a colloidal silica dispersion (manufactured by Nissan Chemical: ST-OL) was used as the dispersion containing the functional particles, and the properties were evaluated.

[0132] Experimental Example 5

[0133] Fumed silica (Aerosil 300 manufactured by AEROSIL Co., Ltd., Japan) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0134] Experimental Example 6

[0135] Fumed silica (Aerosil 200 manufactured by AEROSIL Co., Ltd., Japan) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0136] Experimental Example 7

[0137] Fumed silica (Aerosil 130 manufactured by AEROSIL Co., Ltd., Japan) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0138] Experimental Example 8

[0139] Fumed silica (Aerosil 50, manufactured by AEROSIL Co., Ltd., Japan) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0140] Experimental Example 9

[0141] The fluorescence quantum efficiency was measured in the state of the precursor particle dispersion prepared in the same manner as in Experimental Example 1. For this sample, the fluorescence quantum efficiency in the state of the dispersion was taken as the quantum efficiency before the durability test. Then, the dispersion was placed in a constant temperature and humidity chamber, and the characteristics were evaluated after 100 hours.

[0142] Experimental Example 10

[0143] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that a zirconium oxide sol dispersion (manufactured by Daiichi Kinzo Chemical Industry Co., Ltd.: ZSL00014) was used as the dispersion containing the functional particles, and the properties were evaluated.

[0144] Experimental Example 11

[0145] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that an alumina sol dispersion (Bairaru Al-L7 manufactured by Taki Chemical Co., Ltd.) was used as the dispersion containing the functional particles, and the properties were evaluated.

[0146] Experimental Example 12

[0147] A nanoparticle composite was obtained by the same method as in Experimental Example 1 except that titanium dioxide sol (TAINOC AM-15 manufactured by Taki Chemical Co., Ltd.) was used as the dispersion liquid containing the functional particles, and the properties were evaluated.

[0148] Experimental Example 13

[0149] Fumed alumina (Aerosil Co., Ltd.: Alu-C) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0150] Experimental Example 14

[0151] Fumed titanium dioxide (TiO2 P90 manufactured by AEROSIL Co., Ltd., Japan) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles in such a manner that the concentration of the functional particles was 4 wt.%. In addition, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0152] Experimental Example 15

[0153] Magnesium hydroxide (manufactured by FUJIFILM) was used as the functional particles, and water was added as the dispersion medium to prepare a dispersion containing the functional particles so that the concentration of the functional particles was 4 wt.%. Except for this, a nanoparticle composite was obtained by the same method as in Experimental Example 1, and the characteristics were evaluated.

[0154] Experimental Example 16

[0155] The core of the nanoparticles in Experimental Example 1 was changed to InP by the following method.

[0156] <Preparation of Core (InP)>

[0157] Indium acetate (0.3 mmol) was added to a mixture of oleic acid (0.9 mmol) and octadecene (10 mL), heated to about 120°C under vacuum (<20 Pa), and reacted for 1 hour. The mixture reacted under vacuum was placed at 25°C and nitrogen atmosphere, tri(trimethylsilyl)phosphine (0.2 mmol) was added, and heated to about 300°C and reacted for 10 minutes. The reaction solution was cooled to 25°C, octanoyl chloride (0.45 mmol) was injected, and after heating at about 250°C for 30 minutes, it was cooled to 25°C to obtain an InP nanocrystal solution.

[0158] As functional particles, silica sol (MEK-EC-2130 manufactured by Nissan Chemical) having epoxy groups on the surface was used. The remaining steps were the same as those in Experimental Example 1 to obtain a nanoparticle composite, and the properties were evaluated.

[0159] It should be noted that the particle size of the functional particles is calculated using the following method: the BET specific surface area is measured, and the average particle size (BET diameter) is converted from the value using a true sphere model. For powdered materials, the BET specific surface area is directly measured in powder form, and the average particle size (BET diameter) is calculated from the value. After the particles of the functional particles that are already in a dispersed liquid state are dried once, the BET specific surface area of ​​the dried body is measured, and the average particle size (BET diameter) is calculated from the value.

[0160] Next, the obtained nanoparticle complex was subjected to thermogravimetric differential thermal analysis. The thermogravimetric differential thermal analysis was performed using TG-DTA2000SA manufactured by Buruker. A given amount of sample was placed in a sample holder, N2 was introduced at 200 mL / min, and the sample was heated to 550°C at 10°C / min to perform thermogravimetric measurement and differential thermal analysis of the nanoparticle complex.

[0161] For comparison, a dried product of the functional particles alone (colloidal silica dispersion (Nissan Chemical Co., Ltd.: ST-OXS)) was also subjected to thermogravimetric and differential thermal analysis under the same conditions.

[0162] The results of the mass reduction when the thermogravimetric analysis of Experimental Example 1, Experimental Example 9 and the functional particle monomer are performed are shown. Figure 4 The graphs are superimposed after normalization such that the ligand amount in Experimental Example 1 is equal to the ligand amount in Experimental Example 9 and further normalization such that the amount of the functional particle in Experimental Example 1 is equal to the amount of the functional particle alone.

[0163] Figure 4 In the experiment, a mass reduction was also observed for the functional particle monomer. The inventors believe that this is because the moisture attached to the functional particles gradually detached due to heating. Based on this, when comparing the results of Experimental Example 1 and Experimental Example 9, it can be seen that in Experimental Example 9, all ligands detached until 550°C, while in Experimental Example 1, the detachment of ligands was less than that of Experimental Example 9. Considering the mass reduction in the functional particle monomer, the amount of ligand detachment in Experimental Example 1 until 550°C can be suppressed to less than 20% compared with the amount of ligand detachment in Experimental Example 9.

[0164] Figure 5A to Figure 5E The results of differential thermal analysis of each nanoparticle complex are shown. ΔTG represents the change in TG per unit time in each temperature range. The ΔTG graph indicates the temperature at which the ligand is easily detached. Figure 5A This is a graph showing ΔTG of Experimental Example 9, which has a large valley with a peak at 220°C. This means that the nanoparticle complex of Experimental Example 9 has a large amount of ligand detachment around 220°C. On the other hand, Figure 5BΔTG of Experimental Example 1 is a graph showing the ΔTG of Experimental Example 1. The ΔTG of Experimental Example 1 has a peak value at around 400°C and has a gentle valley. This means that the detachment of the ligand is suppressed by the functional particles, which means that the detachment of the ligand also occurs at high temperatures. Similarly, Figure 5C , Figure 5D , Figure 5E The results of differential thermal analysis of Experimental Example 10, Experimental Example 11, and Experimental Example 12 are shown respectively.

[0165] Table 1 shows the peak temperature of the valley of ΔTG measured by differential thermal analysis in each experimental example.

[0166] It can be seen that the peak temperature of the valley of Experimental Example 9 is 220°C, while the peak temperature of the valley of other Experimental Examples is above 240°C. It can be seen that the detachment of the ligand can be suppressed by having the structure of the present invention. Therefore, in the case of the nanoparticle composite of the present invention, for example, by including silica particles and particles other than silica particles as functional particles, the silica particles can improve weather resistance, and the particles other than silica particles can have other functions.

[0167] [Table 1]

[0168]

[0169] This application includes the following inventions.

[0170] The invention (1) described in the present application is a nanoparticle complex comprising: a nanoparticle; a ligand that is bound to the nanoparticle; and a functional particle that is bound to the nanoparticle via the ligand, wherein the nanoparticle complex has a structure in which the functional particle surrounds the nanoparticle.

[0171] The invention (2) described in the present application is a nanoparticle complex in which a nanoparticle is enclosed in a cohesive structure composed of a plurality of functional particles, and the nanoparticle is bound to the cohesive structure via a ligand.

[0172] Invention (3) described in the present application is a nanoparticle complex according to invention (1) or (2), wherein the ligand has: a nanoparticle binding group that binds to the nanoparticle; and a functional particle binding group that binds to the functional particle.

[0173] Invention (4) described in the present application is a nanoparticle complex according to invention (3), wherein the ligand is bound to the nanoparticle via the nanoparticle binding group and is bound to the functional particle via the functional particle binding group.

[0174] Invention (5) described in the present application is the nanoparticle complex according to invention (3) or (4), wherein the nanoparticle binding group is monodentate.

[0175] Invention (6) described in the present application is a nanoparticle complex according to any one of inventions (3) to (5), wherein the nanoparticle binding group is any one selected from a thiol group, an amino group, a carboxyl group, a phosphate group, a sulfone group, an imide group, an amide group, and a cyanate group.

[0176] Invention (7) described in the present application is the nanoparticle complex according to any one of Inventions (3) to (6), wherein the nanoparticle binding group is a thiol group or an amino group.

[0177] Invention (8) described in the present application is the nanoparticle complex according to any one of Inventions (3) to (7), wherein the functional particle-binding group is a carboxyl group or a hydroxyl group.

[0178] Invention (9) described in the present application is the nanoparticle composite according to any one of Inventions (1) to (8), wherein the ligand contains mercaptopropionic acid or thioglycolic acid.

[0179] Invention (10) described in the present application is the nanoparticle composite according to any one of Inventions (1) to (9), wherein the functional particles are silica particles.

[0180] Invention (11) described in the present application is the nanoparticle composite according to any one of Inventions (1) to (9), wherein the functional particles include silica particles.

[0181] Invention (12) described in the present application is the nanoparticle complex according to any one of Inventions (1) to (11), wherein the nanoparticles are quantum dots.

[0182] Invention (13) described in the present application is the nanoparticle composite according to any one of Inventions (1) to (12), wherein the nanoparticles contain Zn on the surface.

[0183] The invention (14) described in the present application is a nanoparticle complex described in any one of the inventions (1) to (13), wherein the nanoparticle is any one of the following quantum dots: CdS / ZnSe with a core-shell structure in which the core is CdS and the shell is ZnSe, CdSe / ZnSe with a core-shell structure in which the core is CdSe and the shell is ZnSe, CdS / ZnSe / ZnS with a core-shell structure in which the core is CdS and the first shell is ZnSe and the second shell is ZnS, CdSe / ZnSe / ZnS with a core-shell structure in which the core is CdSe and the first shell is ZnSe and the second shell is ZnS, InP / ZnSe with a core-shell structure in which the core is InP and the shell is ZnSe, and InP / ZnSe / ZnS with a core-shell structure in which the core is InP and the first shell is ZnSe and the second shell is ZnS.

[0184] The invention (15) described in the present application is a nanoparticle complex according to any one of the inventions (1) to (14), wherein the nanoparticle is a quantum dot containing Zn on the surface, the ligand has a thiol group as a nanoparticle binding group capable of forming a Zn-S bond on the surface of the nanoparticle, and has a carboxyl group or a hydroxyl group as a functional particle binding group, and the functional particle is a silica particle having a hydroxyl group.

[0185] The invention (16) described in the present application is a dispersion liquid containing the nanoparticle composite according to any one of the inventions (1) to (15).

[0186] The invention (17) described in the present application is a film comprising the nanoparticle composite according to any one of the inventions (1) to (15).

[0187] The invention (18) described in the present application is a medical marker using the nanoparticle complex according to any one of the inventions (1) to (15).

[0188] Furthermore, this application includes the following inventions.

[0189] The invention [1] described in the present application is a method for producing a nanoparticle composite, which comprises:

[0190] A step of combining the nanoparticles and the ligand in a dispersion containing the nanoparticles and the ligand to obtain a precursor particle dispersion; and

[0191] A step of mixing and reacting a dispersion containing functional particles with the precursor particle dispersion to obtain a nanoparticle complex dispersion in which the functional particles are bound to the nanoparticles via the ligand.

[0192] Invention [2] described in the present application is a method for producing a nanoparticle complex according to invention [1], wherein the ligand has:

[0193] a nanoparticle binding group bound to the nanoparticle; and

[0194] A functional particle binding group is bound to the functional particle.

[0195] Invention [3] described in the present application is the method for producing a nanoparticle complex according to invention [2], wherein the functional particle binding group has a carboxyl group and a hydroxyl group.

[0196] Invention [4] described in the present application is the method for producing a nanoparticle complex according to invention [2] or [3], wherein the nanoparticle binding group has a thiol group.

[0197] Invention [5] described in the present application is a method for producing a nanoparticle complex according to any one of Inventions [1] to [4], comprising: after obtaining the nanoparticle complex dispersion, drying the nanoparticle complex dispersion.

[0198] Invention [6] described in the present application is the method for producing a nanoparticle composite according to any one of Inventions [1] to [5], wherein the precursor dispersion liquid is aqueous.

[0199] Invention [7] described in the present application is the method for producing a nanoparticle composite according to any one of Inventions [1] to [6], wherein the dispersion liquid containing the functional particles is aqueous.

[0200] Invention [8] described in the present application is the method for producing a nanoparticle composite according to any one of Inventions [1] to [7], wherein the functional particles are silica particles.

[0201] Invention [9] described in the present application is a method for producing a nanoparticle complex according to any one of Inventions [1] to [8], wherein the nanoparticles are quantum dots.

[0202] Invention

[10] described in the present application is the method for producing a nanoparticle composite according to any one of Inventions [1] to [9], wherein the nanoparticles are nanoparticles containing Zn on the surface.

[0203] Invention

[11] described in the present application is a method for producing a nanoparticle complex according to any one of Inventions [1] to

[10] , wherein the ligand comprises mercaptopropionic acid or thioglycolic acid.

[0204] The invention

[12] described in the present application is a method for producing a nanoparticle complex according to any one of the inventions [1] to

[11] , wherein the nanoparticles are quantum dots containing Zn on the surface, the ligands have a thiol group as a nanoparticle binding group capable of forming a Zn-S bond on the surface of the nanoparticles, and have a carboxyl group or a hydroxyl group as a functional particle binding group, and the functional particles are silica particles having hydroxyl groups.

[0205] The invention

[13] described in the present application is a nanoparticle dispersion liquid, which can generate a nanoparticle complex by mixing and reacting with a dispersion liquid containing functional particles, wherein:

[0206] The nanoparticle dispersion comprises nanoparticles and ligands,

[0207] The ligand has a nanoparticle binding group and a functional particle binding group,

[0208] The nanoparticles are dispersed in a state of being bound to the ligand via the nanoparticle binding groups.

[0209] Invention

[14] described in the present application is the nanoparticle dispersion according to invention

[13] , wherein the functional particle binding group is a carboxyl group or a hydroxyl group.

[0210] Invention

[15] described in the present application is the nanoparticle dispersion according to invention

[13] or

[14] , wherein the nanoparticle dispersion is aqueous.

[0211] The invention

[16] described in the present application is a method for obtaining nanoparticles bound with the ligand, which comprises mixing the ligand with the nanoparticles to obtain nanoparticles bound with the ligand, wherein the ligand has a nanoparticle binding group bound to the nanoparticles and a functional particle binding group bound to the functional particles.

[0212] Invention

[17] described in the present application is a method for obtaining nanoparticles according to invention

[16] , wherein the nanoparticles to which the ligand is bound are mixed with functional particles.

[0213] The invention

[18] described in the present application is a method for obtaining functional particles bound to the ligand, which comprises mixing the ligand and the functional particles to obtain functional particles bound to the ligand, wherein the ligand has a nanoparticle binding group that binds to the nanoparticles and a functional particle binding group that binds to the functional particles.

[0214] Invention

[19] described in the present application is a method for obtaining functional particles according to invention

[18] , wherein the functional particles to which the ligand is bound are mixed with nanoparticles.

[0215] The invention

[20] described in the present application is a method for producing a nanoparticle complex, comprising: a step of mixing and reacting a dispersion containing functional particles and a dispersion containing ligand-bound nanoparticles.

[0216] The invention

[21] described in the present application is a method for producing a nanoparticle complex, comprising: mixing and reacting a dispersion containing functional particles, a ligand, and a dispersion containing nanoparticles.

[0217] The invention

[22] described in the present application is a method for producing a nanoparticle complex, comprising: mixing and reacting a dispersion containing nanoparticles and a dispersion containing functional particles bound to a ligand.

[0218] The invention

[23] described in the present application is a method for obtaining a nanoparticle complex dispersion, which comprises reacting nanoparticles bound with ligands with functional particles to obtain a nanoparticle complex dispersion in which the functional particles are bound to the nanoparticles via the ligands.

[0219] The invention

[24] described in the present application is a method for obtaining a nanoparticle complex, which comprises reacting a functional particle to which a ligand is bound with a nanoparticle to obtain a nanoparticle complex in which the functional particle is bound to the nanoparticle via the ligand.

[0220] The invention

[25] described in the present application is a method for obtaining a nanoparticle complex, which comprises reacting nanoparticles, ligands and functional particles to obtain a nanoparticle complex in which the functional particles are bound to the nanoparticles via the ligands.

[0221] Explanation of symbols

[0222] 11Nano particles 13Functional particles

[0223] 12 ligands 14 condensed structures

Claims

1. A nanoparticle composite comprising: Nanoparticles; a ligand that is bound to the nanoparticle; and Functional particles, which are bound to nanoparticles via the ligands, The nanoparticle complex has a structure in which the functional particles surround the nanoparticles.

2. A nanoparticle complex, wherein: The nanoparticles are enclosed in a cohesive structure composed of a plurality of functional particles, and the nanoparticles are bound to the cohesive structure via a ligand.

3. The nanoparticle complex according to claim 1 or 2, wherein The ligand has: a nanoparticle binding group bound to the nanoparticle; and A functional particle binding group is bound to the functional particle.

4. The nanoparticle complex according to claim 3, wherein The ligand is bound to the nanoparticle via the nanoparticle binding group, and is bound to the functional particle via the functional particle binding group.

5. The nanoparticle complex according to claim 3 or 4, wherein The nanoparticle binding group is monodentate.

6. The nanoparticle composite according to any one of claims 3 to 5, wherein The nanoparticle binding group is any one selected from a thiol group, an amino group, a carboxyl group, a phosphate group, a sulfone group, an imine group, an imide group, an amide group and a cyanate group.

7. The nanoparticle composite according to any one of claims 3 to 6, wherein The nanoparticle binding group is a thiol group or an amino group.

8. The nanoparticle composite according to any one of claims 3 to 7, wherein The functional particle binding group is a carboxyl group or a hydroxyl group.

9. The nanoparticle composite according to any one of claims 1 to 8, wherein The ligand comprises mercaptopropionic acid or thioglycolic acid.

10. The nanoparticle composite according to any one of claims 1 to 9, wherein The functional particles are silicon dioxide particles.

11. The nanoparticle composite according to any one of claims 1 to 9, wherein The functional particles include silicon dioxide particles.

12. The nanoparticle composite according to any one of claims 1 to 11, wherein The nanoparticles are quantum dots.

13. The nanoparticle composite according to any one of claims 1 to 12, wherein The nanoparticles comprise Zn on the surface.

14. The nanoparticle composite according to any one of claims 1 to 13, wherein The nanoparticles are any quantum dots selected from the following: CdS / ZnSe core-shell structure with CdS as the core and ZnSe as the shell; CdSe / ZnSe with a core-shell structure in which the core is CdSe and the shell is ZnSe; CdS / ZnSe / ZnS of a core-shell structure in which the core is CdS, the first shell is ZnSe, and the second shell is ZnS; CdSe / ZnSe / ZnS of a core-shell structure in which the core is CdSe, the first shell is ZnSe, and the second shell is ZnS; InP / ZnSe core-shell structure with InP as the core and ZnSe as the shell; and InP / ZnSe / ZnS of a core-shell structure in which the core is InP, the first shell is ZnSe, and the second shell is ZnS.

15. The nanoparticle composite according to any one of claims 1 to 14, wherein The nanoparticles are quantum dots containing Zn on the surface. The ligand has a thiol group capable of forming a Zn-S bond on the surface of the nanoparticle as a nanoparticle binding group, and has a carboxyl group or a hydroxyl group as a functional particle binding group, The functional particles are silica particles having hydroxyl groups.

16. A dispersion comprising: The nanoparticle composite according to any one of claims 1 to 15.

17. A film comprising: The nanoparticle composite according to any one of claims 1 to 15. 18 . A medical marker using the nanoparticle complex according to claim 1 .

Citation Information

Patent Citations

  • Inorganic NANO phosphor particle complex and wavelength conversion member

    JP2018080272A

  • Quantum dot, method of producing the same, resin composition, wavelength conversion material, and light-emitting element

    JP2019099694A

  • Resin dispersion of quantum dot

    JP2021182025A

  • Method for analyzing polymeric material structure and polymeric material

    JP2022144107A

  • Active noise controller

    JP2022144110A